Collective and individual responsibility : a description of corporate personality in Ezekiel 18 and 20 - Mol, Jurrien. (Studia Semitica Neerlandica, 2009)
A long discussed theme concerning Ezekiel 18 and 20 is the relationship between collective and individual responsibility. In the first half of the twentieth century the discussion appeared to end as a result of the introduction of the corporate personality by Henry Wheeler Robinson (1872-1945). This concept became heavily discussed and was dismissed on the grounds of its superseded theoretical basis. The continuing use of the concept requires a redefinition and a new theoretical basis which is provided by the multimodal framework by Geoffrey Samuel from the field of cultural anthropology. Before applying the concept, Ezekiel 18 and 20 are studied extensively relative to textual criticism, philology, grammar, and structural analysis.